The Regional and International spheres of Algerian Foreign Policy: Diffusion, Performance, and Influence. - BOUKARRAS, Roukaia (Social Empowerment Journal, 2024)
Algeria’s foreign policy operates within the regional and international spheres to which it belongs: it is influenced by them and also exerts influence on them in a mutually dependent regional relationship. Algeria aims to play the role of a influential regional power. However, it faces various challenges arising from increased competition and pressures in the regions that constitute its strategic depth and vital area. To address these challenges, Algerian decision-makers seek to adopt a comprehensive and adaptable strategy that enhances their influence, performance, and reach. They employ proactive and dynamic diplomacy that reaffirms their steadfast stance on the Palestinian cause, liberation movements, and just issues. Algeria also seeks to revive inter-Maghreb cooperation in the region, supported by its non-permanent membership in the United Nations Security Council until December 2025. This has positioned Algeria as a key player in both local and international arenas. Algeria works towards achieving a strong positioning within the sub-regions it belongs to by enhancing its role as a trusted mediator in Middle Eastern issues. It focuses on strengthening its relationships with Arab (and Maghreb), Mediterranean, and African countries through innovative solutions. Algeria possesses elements of latent power, including energy, economy, demographics, and strong political will, which contribute to its pursuit of a robust regional presence.